Angiotensin‐(1‐7) improves non‐alcoholic steatohepatitis through an adiponectin‐independent mechanism. Issue 1 (28th April 2016) - Tang, Ailian; Li, Can; Zou, Nan; Zhang, Qian; Liu, Meiling; Zhang, Xia
Abstract : Aim: Recent evidence suggests that angiotensin‐(1‐7) [Ang‐(1‐7)] could improve non‐alcoholic steatohepatitis (NASH) through an adiponectin‐dependent mechanism. This study aimed to investigate whether and how Ang‐(1‐7) influences NASH without adiponectin. Methods: Adiponectin knockout mice were fed with a high fat diet (HFD) or normal chow for 6 months, and were subsequently infused with Ang‐(1‐7) or saline for 2 weeks. Results: We found that HFD‐fed mice showed obesity, hyperlipidemia, NASH, and significantly increased levels of serum Ang‐(1‐7). Chronic infusion of Ang‐(1‐7) could reduce body weight, absolute and relative liver weight, and serum levels of total cholesterol, triglyceride, and low‐density lipoprotein cholesterol in HFD‐fed mice. In addition, Ang‐(1‐7) treatment could attenuate hepatocellular inflammation, steatosis, and ballooning with activation of the hepatic AMP‐activated protein kinase signaling pathway in HFD‐fed knockout mice. Conclusions: These results showed the protective role of Ang‐(1‐7) in the development of NASH through an adiponectin‐independent mechanism, which may be partially attributed to the activation of hepatic AMP‐activated protein kinase pathway.